Seasonal abundance of montandoneilla moraguesi puton (Hemiptera: Anthocoridae), the predator of Gynaikothrips ficorum marchal (Thysanoptera: Phloethripidae) on Ficus nitida Thunb. at Giza, Egypt - Ibrahim, Maha M. A.; Tawfik, M. F. S.; Agamy, E. A.; EI Husseini, M. M.
Montandoniella moraguesi Puton (Hemiptera: Anthocoridac) is a specific predator of the laural thrips, Gynaikothrips ficorum Marchal, infesting Ficus nitida Thwnb. trees. In Egypt, the predator was found at Giza region throughout the year. Populations of its nymphs and adults assured its role in suppressing the population of the thrips, G. ficorum Both the predator and the prey showed 4 peaks! year, with much higher populations in autumn, winter and spring than in summer.
Includes references.
1
Keywords: Biological pest control agents; Weeping fig -- Diseases and pests; Predatory insects; Insects as biological pest control agents; Gynaikothrips; Gynaikothrips ficorum